Dari Sampah Jadi Karya: Inovasi Mathematic Aquaponik untuk Ketahanan Pangan dan Gaya Hidup Berkelanjutan - Fury Styo Siskawati; Sholahudin Al Ayubi; Endang Sri Wahyuni; Nabila Rizqi Ananda; Putri Sholehah; Muhammad Saiful Rizal (Al-Khidmah Jurnal Pengabdian Masyarakat, 2026)
This community service activity aims to enhance public awareness and skills in managing plastic waste through a creative innovation that integrates science and art, namely the development of Mathematic Aquaponics. The program was carried out by a team of lecturers and students from the Mathematics Education Study Program, Faculty of Teacher Training and Education (FKIP), Universitas Islam Jember, in collaboration with teachers and students of SMK Nailul Huda Mrawan Tapen Bondowoso. The activity began with a socialization session on the impact of plastic waste and the principles of reduce, reuse, recycle (3R), followed by a workshop on creating a simple aquaponic system using recycled materials such as used plastic bottles, drink cups, and damaged water gallons. The Participatory Action Research (PAR) approach was employed to ensure active participant involvement at every stage, including the application of basic mathematical calculations to determine water volume, the ratio of plants to fish, and geometric spacing in the system design. The results showed an increase in participants’ knowledge and creativity, with 92% successfully redesigning their own Mathematic Aquaponic systems that combined functional and aesthetic aspects. This program demonstrates that plastic waste can be transformed into a contextual learning medium integrating mathematics education, environmental science, and sustainability values. Thus, the activity not only contributes to reducing plastic waste but also fosters a scientific and creative culture within schools and communities.